Responding to Failure: The Responsibility to Protect after Libya. (June 2016) - Hobson, Christopher
During its first decade in existence, the Responsibility to Protect (R2P) doctrine has struggled to transcend the complexities that plague humanitarian action. This article examines the political challenges that shape the practice of R2P, as well as the discourse that informs it. It reflects on the constant presence of failure that haunts humanitarian intervention, and argues for a more humble stance on what is possible in such situations. Humility entails meditating on human limits, both physical and mental, which serves as an important guide in determining action. It promotes a more chastened position; one that acknowledges that right intentions might not lead to just outcomes, that there are real limits on the ability of external actors to understand or control events during and following an intervention, and that our ability to comprehend such complex situations should warn against premature judgements and confident conclusions. And when failure occurs, it means not denying or avoiding it, but facing it squarely and reckoning with the consequences. The value of adopting a more humble approach will be considered through examining the 2011 Libyan intervention, a significant case for the R2P doctrine. There, success appears to have been exchanged for failure, leaving challenging and unresolved questions about what this experience means for Libya and R2P.